Mid-term outcome and quality of life after Bentall procedure: single-center experience - I. O. Stetsyuk; L. R. Stetsiuk; B. M. Todurov; I. Yu. Mokryk; V. I. Zaviiskyi; I. P. Nechai; V. B. Demyanchuk; O. V. Zelenchuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the mid-term results and quality of life of patients who underwent Bentall procedure. Materials and methods. The research included 55 patients who underwent planned surgical treatment at the Heart Institute of Ministry of Health of Ukraine from 2015 to 2023. The mean age of the 55 patients (53 (96.36 %) males), who underwent the Bentall procedure (composite graft replacement of the aortic root), was 52.36 ± 1.56 years. We analyzed basic characteristics of the patients, intraoperative and postoperative data. The quality of life was assessed before and in the mid-term period after operations by the Medical Outcomes Study Short Form 36 (MOS SF-36) questionnaire. Results. An average duration of the follow-up period was (3.61 ± 0.28) (СІ 3.05–4.16) years ranging from 1.0 to 9.0 years. Overall, in-hospital mortality and 30-day mortality was 1.89 % (n = 1). The only case of death was caused by the acute respiratory distress syndrome. The 5-year survival rate was 94.61 ± 3.10 % for all patients. It is reasonable to say that all 3 cases of death were due to a non-cardiac cause, i.e. stroke, malignancy and acute abdomen. The average duration of the operations was 244.48 ± 7.67 minutes, the total duration of artificial blood circulation was 138.73 ± 6.47 minutes, aorta clamping time – 95.82 ± 4.79 minutes. The mean duration of hospital staying was 16.98 ± 0.91 days, intensive care unit – 4.84 ± 0.33 days. The number of patients extubated up to 8 hours after surgery was 41 (74.55 %) patients. The operation significantly improved parameters of the quality of life. Conclusions. Patients after Bentall procedure have low overall in-hospital mortality and 30-day mortality (1 (1.89 %)). The 5-year survival rate was 94.61 ± 3.10 %. All three case of death during follow-up period were due to non-cardiac causes. Excellent mid-term results prove that Bentall procedure must be a routine surgery for patients with aortic root aneurysm, mixed aortic valve pathology and anatomically altered aortic valve leaflets. The operation significantly improved quality of life of patients in all domains.